Significance of sediment transport processes during piedmont floods: the 2005 flood events in Switzerland. Issue 2 (14th October 2015) - Rickenmann, Dieter; Badoux, Alexandre; Hunzinger, Lukas
Abstract: A long‐lasting rainstorm event from 20 to 22 August 2005 affected a large part of the northern Alps and Prealps in Switzerland. It resulted in elevated discharges and flooding in many headwater catchments and mountain rivers. The associated geomorphic processes included shallow landslides, deep‐seated slope instabilities, debris flows, and fluvial sediment transport. In many parts of the affected areas human activities are important, including many buildings, traffic lines and other infrastructure. In the steeper parts, geomorphic processes were mainly responsible for flow overtopping and sediment deposition both in and outside of the channel network. In the lower parts, lateral erosion and exceedance of the channel discharge capacity were the main reasons for morphologic channel modification and flooding. Sediment‐related processes contributed a lot to the overall damage. Copyright © 2015 John Wiley & Sons, Ltd.